Arahan Pengendalian Alih Fungsi Lahan Daerah Resapan Air di Kelurahan Batua, Kecamatan Manggala Kota Makassar - Pratama, Ramanda; Aksa, Kamran; Jaya, Baso (Journal of Urban Planning Studies, 2024)
This research aims to determine the water catchment areas in Batua Village, Manggala District, Makassar City and to formulate control over land conversion of water catchment areas in Batua Village, Manggala District, Makassar City. This research is used as consideration and reference material in quantitative analysis. The variables in this research include topography, population, land value, accessibility, facilities and infrastructure, and environmental carrying capacity. The analysis methods used in this research are Correlation Analysis and SWOT Analysis. In terms of the influence of population, land value, accessibility, on land conversion. The strategy used to formulate control over land conversion is utilizing policies to stabilize the growth of facilities and infrastructure in Batua Village, arranging facilities and infrastructure based on the 2015-2034 Makassar City RTRW and structuring residential areas based on the 2015-2034 Makassar City RTRW.